Hypoglycemic Effects of Rosa damascena Mill. Ethanolic Extract on Blood Glucose Levels and Diameter of Langerhans Pancreatic Islets - Bilqis Inayatillah; Tamam Jauhar; Gondo Mastutik; Alphania Rahniayu (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Diabetes mellitus is a chronic disorder caused by elevated levels of high blood glucose(hyperglycemia). This chronic hyperglycemia causes ROS to accumulate and oxidative stress to increase.Rosa damascena is a plant that contains high levels of antioxidants and polyphenols, but this is not widelyknown to the public. Purpose: The aim of this study is to understand the hypoglycemic effects from Rosadamascena on blood glucose levels and diameter of Langerhans pancreatic islets. Method: Thirty Wistaralbino rats (200-225gr) were divided into 6 groups. Group 1 was a normal control (KN), group 2 washyperglycemic (KD), group 3 was metformin 250 mg/kg BW (KM), group 4 was treatment extract 250 mg/kg BW (P1), group 5 was treatment extract 500 mg/kg BW (P2) group 6 was treatment extract 1000 mg/kg BW (P3). All animals in the group were injected with STZ 50 mg/kg BW, except for group 1. Result:Data were analyzed statistically using SPSS- 22 software with the Kruskall-Wallis test (p<0.05). The resultshowed that ethanolic extract of Rosa damascena has decreased blood glucose levels in days-14 (382±21,97) with 250 mg/kg BW (P1) compare with another treatment group. In histological observed there areno significant different between group (p>0.05). This is showing that ethanolic extract of Rosa damascenahas inability to repaired the diameter of Langerhans pancreatic islets. Conclusion: Ethanolic extract of Rosadamascena decreased blood glucose levels but did not repaired the diameter of Langerhans pancreatic islets.